Transforming growth factor β cooperates with persephin for dopaminergic phenotype induction - Roussa, Eleni; Heermann, Stephan (Stem cells, 2008)
The aim of the present study was to investigate the putative cooperative effects of transforming growth factor β (TGF-β) and glial cell line-derived neurotrophic factor (GDNF) family ligands in the differentiation of midbrain progenitors toward a dopaminergic phenotype. Therefore, a mouse midbrain embryonic day (E) 12 neurospheres culture was used as an experimental model. We show that neurturin and persephin (PSPN), but not GDNF, are capable of transient induction of dopaminergic neurons in vitro. This process, however, requires the presence of endogenous TGF-β. In contrast, after 8 days in vitro GDNF rescued the TGF-β neutralization-dependent loss of the TH-positive cells. In vivo, at E14.5, no apparent phenotype concerning dopaminergic neurons was observed in Tgf-β2−/−/gdnf−/− double mutant mice. In vitro, combined TGF-β/PSPN treatment achieved a yield of approximately 20% TH-positive cells that were less vulnerable against 1-methyl-4-phenyl pyridinium ion toxicity. The underlying TGF-β/PSPN differentiation signaling is receptor-mediated, involving p38 mitogen-activated protein kinase and phosphatidylinositol 3-kinase pathways. These results indicate that phenotype induction and survival of fully differentiated neurons are accomplished through distinct pathways and individual factor requirement. TGF-β is required for the induction of dopaminergic neurons, whereas GDNF is required for regulating and/or maintaining a differentiated neuronal phenotype. Moreover, this study suggests that the combination of TGF-β with PSPN is a potent inductive cocktail for the generation of dopaminergic neurons that should be considered in tissue engineering and cell replacement therapies for Parkinson's disease. Disclosure of potential conflicts of interest is found at the end of this article.